Effect of a Seasonal Fishery Closure on Sardine and Mackerel Catch in the Visayan Sea, Philippines - Bagsit, Farisal U.; Frimpong, Eugene; Asch, Rebecca G.; Monteclaro, Harold M. (Frontiers in Marine Science, 2021)
The implementation of seasonal fishery closures (SFC) can be controversial due to the frequent lack of clear objectives, monitoring and empirical evidence of management success. In the Philippines, an SFC implemented for the conservation of important fishery commodities in the Visayan Sea has been ruled a success after stricter implementation of this fishery policy in 2012. However, a comprehensive, detailed, and robust analysis of this fishery policy is lacking. Using a difference-in-differences (DID) framework, we estimated the effect of SFC on the interannual and seasonal catch for sardine and mackerel. We expanded our analysis to other species not regulated under the SFC policy. We also conducted semi-structured interviews (N = 235), focus group discussions (N = 9) and key informant interviews (N = 37) involving municipal fisheries stakeholders in the surrounding municipalities around the Visayan Sea, and representatives from the government and non-government agencies, to complement our analyses. Seasonal analyses of catch data show a significant increase in sardine catch at the end of the seasonal closure among SFC-participating provinces. However, overall, the SFC had no significant effect on sardine interannual catch among the provinces participating in the SFC. We also found no significant effect of the SFC on interannual and seasonal catch for mackerel. Furthermore, our findings show no significant changes in fishing pressure to other aquatic species. Interview results corroborate our DID findings for mackerel, but not for sardine. The varying perceptions on the outcomes of the SFC policy can be attributed to several challenges such as lack of implementing guidelines, lack of alternative livelihoods for the affected stakeholders, persistence of illegal fishing, and uneven implementation of the SFC. Since the management objective of this SFC was to conserve the regulated species, alternative management measures may be needed to achieve this goal. This could entail more consistent enforcement, improved cooperation and communication between fisheries managers and stakeholders, fish size or gear restrictions, and identification and conservation of key habitats needed to restore overexploited species.